A longitudinal retrospective analysis of left ventricular mass in a cohort of pediatric kidney transplant recipients. (4th October 2014) - McLaughlin, Robyn; Hamiwka, Lorraine; Samuel, Susan; Fruitman, Deborah; Grisaru, Silviu
Abstract Childhood end‐stage kidney disease is associated with increased risk for early adulthood cardiovascular (CV) morbidity and mortality. Increased LVM is an early indicator of CV disease. Previous studies have suggested that LVM decreases after kidney transplantation; however, trends have been inconsistent. A single center retrospective longitudinal cohort analysis of LVM, documented annually, starting before kidney transplantation for up to 10 yr after transplantation was performed. BP documented by annual 24‐h ambulatory monitoring studies, and BMI values were also reviewed. Twenty‐seven children followed for a mean period of 5.3 yr were included. Depending on definition of LVH, its prevalence pretransplant and in the first years post‐transplant was up to 33% dropping to 0–25% thereafter. Individual longitudinal LVM z‐score trends were highly variable but generally trended toward the mean immediately after transplant and toward negative values in the following years. BP was stable during the follow‐up period while mean annual BMI increased in the first‐year post‐transplant but declined thereafter. In a cohort of pediatric renal transplant recipients, prevalence of LVH decreased after transplant; however, individual longitudinal LVM trends were highly variable among patients. Prospective studies are needed to correlate individual LVM trends with outcomes.